Assessment of sulfur trioxide formation due to enhanced interaction of nitrogen oxides and sulfur oxides in pressurized oxy-combustion. (15th April 2021) - Wang, Xuebin; Yablonsky, Gregory S.; ur Rahman, Zia; Yang, Zhiwei; Du, Pan; Tan, Houzhang; Axelbaum, Richard L.
Highlights: The enhanced SOx-NOx interaction in pressurized oxy-combustion is studied. A nine-step reduced chemistry is developed to estimate SO3 and NO2 formation. The SOx-NOx interaction at elevated pressures significantly accelerates SO3 formation. A group of strong cycle reactions is found dominant for SO3 formation at elevated pressures. Abstract: Pressurized oxy-combustion is emerging to be one of the best technologies for significantly decreasing the energy penalty for CO2 capture in coal-fired power plants. However, the higher pressure boosts the formation of acid gases, including SO3 and NO2, which could increase the risk of corrosion. The synergistic promotion of SO3 and NO2 formation in pressurized oxy-combustion is kinetically evaluated under representative conditions (1 30 atm, 600 1200 °C, NO/SO2 = 0.1 5). We begin with a comprehensive mechanism (72 species and 428 reactions), covering nitrogen and sulfur chemistry, relying on GRI-Mech 3.0. This analysis shows that the interaction of SOX and NOX enhances the conversion rates of SO2 → SO3, and this effect is more apparent at elevated pressures and lower temperatures. Mechanism analyses indicate that at elevated pressures, the formation pathways of SO3 through HOSO2 + O2 = SO3 + HO2, and NO2 through HO2 + NO = NO2 + OH, are promoted due to the strong interaction between SOX and NOX . The intermediate between these two reactions is SO2 + OH + M = HOSO2 + M, resulting in a strong cycle, that can be expressed by the global reaction NO + SO2 + O2 = NO2 + SO3 . Finally, a nine-step reduced chemistry is developed and validated to accurately predict the formation of SO3 in the post-flame region at elevated pressures.